Description of a new species of the genus Xenophrys Günther, 1864 (Amphibia: Anura: Megophryidae) from Mount Jinggang, China, based on molecular and morphological data - Wang, Ying-Yong; Zhang, Tian-Du; Zhao, Jian; Sung, Yik-Hei; Yang, Jian-Huan; Pang, Hong; Zhang, Zhong (Zootaxa, 2012)
A new species, Xenophrys jinggangensis sp. nov., is described based on a series of specimens collected from Mount Jing-gang, Jiangxi Province, Eastern China. The new species can be easily distinguished from other known congeners by mor-phology, morphometrics and molecular data of the mitochondrial 16SrRNA gene. The new species is characterized by itssmall size with adult females measuring 38.4–41.6 mm in snout-vent length and males measuring 35.1–36.7 mm; headlength approximately equal to head width; tympanum large and distinct, about 0.8 times of eye diameter; vomerine teethon two weak ridges; tongue not notched behind; relative finger length II < I < IV < III; slight lateral fringes present ondigits; toes bases with thick, fleshy web; dorsum with tubercles and swollen dorsolateral folds; large pustules scattered on flanks; and unique color patterns. The new species represents the thirty-first known Xenophrys in China.